#TITLE_ALTERNATIVE# - Triyoso (NIM 102 03 021), Kaswandhi
Abstract : Seismic data is generated by waves propagating through a subsurface. The image that is obtained in this process is a distorted image that does not correctly reflect the true geometry of the subsurface structure. The migration process removes this wave propagation effect and as a result seismic events move to their correct subsurface position. Several migration methods are used to obtain the best result that is reflects the true geometry of the subsurface structure. This final project present a technique which is very popular used in migration of seismic data, known as Kirchhoff pre-stack depth migration (PSDM). The goal of pre-stack depth migration is building velocity model. Even in sparse seismic data, Kirchhoff pre-stack depth migration with good velocity model could image seismic data accurate enough with less time consuming.